Postharvest quality of ozonized "nanicão" cv. bananas - Faroni, Lêda Rita D'Antonino; Alencar, Ernandes Rodrigues de; Pinto, Michele da Silva; Costa, André Rodrigues da; Silva, Tales Afonso da (Revista Ciência Agronômica, 2013)
This study was done to analyze the physic-chemical, microbiological and sensory qualities of the banana, after being either dry or wet treatment with ozone. For dry processing, the fruits were directly fumigated with ozone for 30 min. The wet treatment included the ozonization of water for 20 min followed by immersion of the fruit in the ozonized water for 10 min. In both treatments, the utilized gas concentration and flow were 0.36 mg L-1 and 1.5 L min-1, respectively. The quality of the fruits was evaluated at the beginning of storage and after 3; 6; 9 and 12 days. The variables analyzed were: fresh mater loss, total titratable acidity, total soluble solids, pH, pulp/peel ratio, color index of the peel, rot severity, microbiological analysis (total fungi and yeast count) and sensorial analysis. In general, the fruits immersed in the ozonized water presented better quality, in reference to both the physico-chemical and microbiological parameters, as well as have good sensory acceptance among those tested. It could therefore be concluded that treatment with ozonized water is a new alternative for the postharvest handling of bananas.

Esse trabalho teve como objetivo avaliar a qualidade físico-química, microbiológica e sensorial da banana ozonizada por via seca e por via úmida. Para o tratamento por via seca, os frutos foram fumigados diretamente com ozônio por 30 minutos. Para o tratamento da banana por via úmida, efetuou-se a ozonização da água por 20 min, e em seguida imersão dos frutos na água ozonizada por 10 min. Em ambos os tratamentos a concentração do gás e a vazão utilizadas foram 0,36 mg L-1 e 1,5 L min-1, respectivamente. A qualidade dos frutos foi avaliada no início do armazenamento e aos 3; 6; 9 e 12 dias. Analisaram-se as variáveis: perda de massa fresca (PMF), acidez total titulável, sólidos solúveis totais, pH, relação polpa/casca, índice de cor da casca, severidade de podridões, análise microbiológica (contagem total de fungos e leveduras) e análise sensorial. Em geral, os frutos imersos em água ozonizada foram os que apresentaram melhor qualidade ao longo do armazenamento, tanto no que se refere aos parâmetros físico-químicos quanto aos microbiológicos, e tiveram boa aceitação sensorial entre os provadores. Dessa forma, concluiu-se que o tratamento com água ozonizada é uma nova alternativa para manejo pós-colheita de banana.
Keywords: Banana; Fruit-preservation; Food-sensorial analysis; Banana; Frutas-conservação; Alimentos-análise sensorial